Synthesis, characterization, and evaluation of silver(I) complexes with mixed-ligands of thiosemicarbazones and diphenyl(p-tolyl)phosphine as biological agents - Abdul Halim, Syahrina Nur 'Ain; Nordin, Fariza Juliana; Mohd Abd Razak, Mohd Ridzuan; Mohd Sofyan, Nur Rahimah Fitrah; Halim, Siti Nadiah Abdul; Rajab, Nor Fadilah; Sarip, Rozie (Taylor & Francis, 2019)
Five new silver(I) complexes were synthesized with mixed ligands of thiosemicarbazone derivatives and diphenyl(p-tolyl)phosphine in search of new biologically active compounds. A CHN elemental analysis, powder X-ray diffraction (PXRD) data and several spectroscopic techniques such as Fourier-transform infrared spectroscopy, energy-dispersive X-ray, 1 H, 13 C, and 31 P{ 1 H} NMR were performed to elucidate the structure of these complexes. Elemental analysis suggested that the stoichiometry of the complexes formed by the reaction of silver nitrate with thiosemicarbazone in the presence of (p-tolyl)PPh 2 was indeed 1:2:1 molar ratio. The silver ions were discovered to be coordinated to the sulfur of thiosemicarbazone and phosphorus of (p-tolyl)PPh 2 , having a tetrahedral geometry based on the spectroscopic data obtained. The PXRD patterns were studied to see the degree of crystallinity of the complexes. The in vitro antiproliferative activity of these complexes was investigated toward the MDA-MB-231 and MCF-7 breast cancer cell lines, as well as the HT-29 colon cancer cell line, which yielded IC 50 values in low micromolar range. The antiplasmodial activity of these complexes was also examined against chloroquine-resistant Plasmodium falciparum parasite which demonstrated good activity and further tested for their selectivity index. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.